Crop genotype modulates root rot resistance-associated microbial community composition and abundance of key taxa - Valentin Gfeller; Michael Schneider; Natacha Bodenhausen; Matthew W. Horton; Lukas Wille; Klaus H. Oldach; Bruno Studer; Martin Hartmann; Monika M. Messmer; Pierre Hohmann (Environmental Microbiome)
Abstract Background Plants are constantly challenged by pathogens, which can cause substantial yield losses. The aggressiveness of and damage by pathogens depends on the host-associated microbiome, which might be shaped by plant genetics to improve resistance. How different crop genotypes modulate their microbiota when challenged by a complex of pathogens is largely unknown. Here, we investigate if and how pea (Pisum sativum L.) genotypes shape their root microbiota upon challenge by soil-borne pathogens and how this relates to a genotype’s resistance. Building on the phenotyping efforts of 252 pea genotypes grown in naturally infested soil, we characterized root fungi and bacteria by ITS region and 16 S rRNA gene amplicon sequencing, respectively. Results Pea genotype markedly affected both fungal and bacterial community composition, and these genotype-specific microbiota were associated with root rot resistance. For example, genotype resistance was correlated (R2 = 19%) with root fungal community composition. Further, several key microbes, showing a high relative abundance, heritability, connectedness with other microbes, and correlation with plant resistance, were identified. Conclusions Our findings highlight the importance of crop genotype-specific root microbiota under root rot stress and the potential of the plant to shape its associated microbiota as a second line of defense.